Pengaruh Perilaku Wisatawan terhadap Minat Berkunjung ke Wisata Sejarah di Kota Bandung : Studi Kasus Gen Z Kota Bandung - Revaldi Revaldi; Fanny Agustina Hidayat; Ramdani Setiyariski (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to examine the influence of tourist behavior on interest in visiting historical tourist destinations in Bandung, with a focus on Generation Z as a growing potential tourist segment. Tourist behavior in this context is analyzed through four main factors, namely cultural, social, personal, and psychological factors that theoretically can influence tourist decisions in choosing a destination. This study uses a quantitative approach with a descriptive-verification method, where primary data is obtained by distributing questionnaires to respondents included in the Generation Z category and who have or have the potential to visit historical tourist destinations in Bandung. The data analysis technique used is Partial Least Square (PLS), because it is able to test the relationship between variables simultaneously and partially. The results show that tourist behavior simultaneously has a significant effect on interest in visiting historical tourist destinations. However, partial analysis shows that not all factors contribute equally. Social, personal, and psychological factors are proven to have a significant influence on the interest in visiting Generation Z. This indicates that social interaction, lifestyle, individual characteristics, and motivation and psychological needs are more dominant in encouraging Generation Z to choose historical tourism as a destination. On the other hand, cultural factors do not show a significant influence, indicating that cultural background is not a major consideration in Generation Z's travel decisions. This finding provides practical implications for managers of historical tourism destinations in Bandung City, namely the need to develop promotional strategies and service development that emphasize social aspects, personalization of experiences, and fulfillment of the psychological needs of Generation Z. Thus, the appeal of historical tourism can be improved and be more relevant to the preferences of the younger generation.